Slope Stability Analysis Under Dry-Wetting Cycle Conditions (Case Study: Landslide Countermeasure of Batas Pidie/Aceh Besar - Batas Kota Sigli) - Zulfadhli Zulfadhli; Trihanyndio Rendy Satrya; Ria Asih Aryani Soemitro; Fikri Afzal (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2025)
A landslide occurred on National Road Section Bts. Pidie/Aceh Besar - Bts. Kota Sigli Sta. 0+500 during the peak of the rainy season has resulted in the disruption of traffic lanes. Soil samples were obtained from the landslide site for inclusion in the testing process. The laboratory tests encompass a range of physical and mechanical parameters and also dry-wetting procedures. The result shows that the topsoil layer consists of sandy silty clay with medium plasticity. Then, a dry-wetting cycle was conducted to simulate the dry and rainy season by introducing and reducing water content from the initial condition (wi) to saturated (wsat) and to airdried (wairdry) with 25%, 50%, 75%, and 100% interval. The results showed a decrease in unconfined compressive strength (qu) by 22.70% and negative pore water pressure (-Uw) by 53.14%. Slope stability analysis found that the slope was stable after the landslide with an FS value of 1.380 and increased to 1.410 when there was the addition of slab on pile road construction. The addition of rainfall variations for 3 and 5 hours is insignificant to the stability of the slope due to the groundwater table being too deep to affect pore water pressure.